Geographical Variation in Flower Color in the Grassland Daisy Gerbera aurantiaca: Testing for Associations With Pollinators and Abiotic Factors - Johnson, Isabel M.; Edwards, Trevor J.; Johnson, Steven D. (Frontiers in Ecology and Evolution, 2021)
Geographical variation in flower color of a plant species may reflect the outcome of selection by pollinators or may reflect abiotic factors such as soil chemistry or neutral processes such as genetic drift. Here we document striking geographical structure in the color of capitula of the endemic South African grassland daisy Gerbera aurantiaca and ask which of these competing explanations best explains this pattern. The color of capitula ranges from predominantly red in the southwest to yellow in the centre, with some northern populations showing a high level of within-population polymorphism. In mixed color populations, yellow, orange and red morphs were equally attractive to hopliine scarab beetles, the most abundant pollinators, and did not differ significantly in terms of fruit set. Honeybees frequently visited capitula in the yellow population but were seldom observed on red morphs. Beetles were attracted to both red and yellow pan traps, but preferred the latter even at sites dominated by the red morph. We found no strong associations between morph color and abiotic factors, including soil chemistry. Plants grown in a common garden retained the capitulum color of the source population, suggesting that flower color variation is not a result of phenotypic plasticity. These results show that flower color in G. aurantiaca is geographically structured, but the ultimate evolutionary basis of this color variation remains elusive.